Recommendations for Management of Whiteflies, Whitefly-transmitted viruses, and Insecticide Resistance for Production of Cucurbit Crops in Florida - Susan E. Webb; David J. Schuster; Philip A. Stansly; Jane E. Polston; Scott Adkins; Carlye A. Baker; Pamela Roberts; Oscar E. Liburd; Teresia Nyoike; Eugene McAvoy; Alicia Whidden (EDIS, 2011)
Until recently, squash has been the only cucurbit crop seriously affected by the B biotype of the sweet potato whitefly, also known as the silverleaf whitefly, because of the silverleaf disorder induced by feeding of the immature stages (nymphs). However, three viruses transmitted by the whitefly have been identified in watermelon, muskmelon, and squash in Florida since 2004, making whitefly management a priority for most cucurbits. This 8-page fact sheet details the current UF/IFAS recommendations for managing whitefly-transmitted viruses and for delaying the development of resistance to insecticides in the whitefly vector. Published by the UF Department of Entomology and Nematology, July 2011.